Power density improvement due to Rotor Flux screens in an SRM with a higher number of Rotor Poles than Stator Poles - Ali A. Abdelaziz; Khaled H. Ahmed; Ahmed M. Massoud; Barry W. Williams (Renewable Energy and Sustainable Development, 2023)
This paper investigates the effect of rotor flux screens (conducting screens) on the performance of switched reluctance motors with a higher number of rotor poles than stator poles. A high number of rotor poles decreases the torque ripple, which is desirable for electric vehicle applications. The conducting screens fill the rotor interpolar gaps forming a cylindrical rotor hence alleviating the windage losses, especially effective at high speeds. The effect of conducting screen thickness and material electrical conductivity on current rise time, developed torque, and output power is studied. A procedure for calculating the effective value of unaligned inductance for screened motors using the flux tube method is presented. Finite element analysis results for different screen cases confirm the effectiveness of conducting screens in improving the torque, hence power capability, of switched reluctance motors.   Received: 11 January 2023 Accepted: 03 May 2023 Published: 30 May 2023